Oneself in practitioner research, with Vygotsky and Bakhtin. Issue 4 (3rd July 2016) - Gade, Sharada
Abstract: Practitioner action and reflection are understood as central to practitioner research in this paper. While Vygotskian-based premise highlights instructional practices and intervention as central to practitioner understanding, Bakhtin-based dialogical premise draws on relational constructs and attend to practitioner being, answerability and authorship. Vygotskian and Bakhtinian units of analysis used are viewed as means with which to conceive practitioner action/reflection and build a community of practitioners. Taken together, practitioner knowing is found inextricable with practitioner ontology, making practitioner research of ongoing instructional practices more human in line with Dewey.